CREATIVE CONTENT MONETIZATION: CASE STUDIES ON DIGITAL PLATFORMS - Kadeni Kadeni; Ekbal Santoso; Wang Jing (Journal of Social Entrepreneurship and Creative Technology, 2025)
The rise of digital platforms has transformed the way creative content is produced, shared, and consumed, opening up new avenues for content creators to monetize their work. However, despite the rapid growth of digital content, challenges persist in understanding the most effective strategies for monetization. This research aims to explore the various monetization models used by content creators on digital platforms, focusing on case studies across YouTube, Patreon, Instagram, and TikTok. The goal is to identify key factors that contribute to successful content monetization and to analyze the potential for these models to be applied across different types of creative content. A qualitative research approach was used, with in-depth case studies of five content creators from various creative fields, including music, visual arts, and writing. Data were collected through interviews, content analysis, and platform performance metrics. The findings indicate that a combination of audience engagement, consistent content production, and platform-specific strategies (such as ads, subscriptions, and merchandise) were critical to successful monetization. Additionally, creators who diversified their revenue streams were more likely to achieve long-term financial sustainability. The research concludes that the future of creative content monetization lies in the development of personalized, audience-centric models and the integration of emerging technologies like AI and blockchain. These findings provide valuable insights for content creators seeking to optimize their monetization strategies in the ever-evolving digital landscape.